LEVERAGING MUSIC AND SONGS TO ENHANCE LISTENING SKI ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the use of songs and music as a tool for teachinglistening skills, highlighting its benefits for learners of all ages and contexts. It explains whymusic is effective, emphasizing its ability to capture attention, enhance memory, and promoteactive listening. The article also provides practical strategies, such as lyric-focused activities, singing along, and genre exploration, to engage learners and improve their listening abilities. It concludes by discussing the broader advantages of using music, including fostering culturalunderstanding and emotional connection. This resource is valuable for educators, languageinstructors, and anyone interested in innovative teaching methods.